Development of a medication literacy assessment scale for patients with mental disorders in recovery in China: a mixed-methods Delphi study - Deng, Lin; Wu, Bei; Lou, Jianlin; Zhang, Chen; Huang, An; Gu, An; Chen, Haiqin; Wang, Lina (Frontiers in Psychiatry, 2025)
BackgroundPatients with mental disorders often exhibit unique challenges in medication adherence, comprehension of drug information, and self-management abilities, underscoring the need for a specialized assessment tool to accurately reflect their medication literacy levels and support targeted clinical interventions.MethodsA stepwise, mixed-methods design was adopted to develop the Medication Literacy Assessment Scale. Preliminary items were generated through a comprehensive literature review and semi-structured interviews with 20 patients and 6 psychiatric professionals. Then, a two-round Delphi study was conducted to refine the scale based on expert consensus. Quantitative analysis of expert feedback guided the scale’s refinement, ensuring it effectively captures the unique aspects of medication literacy for patients with mental disorders in recovery.ResultsThe finalized Medication Literacy Assessment Scale for patients with mental disorders in recovery was developed, yielding 35 items across four dimensions: functional literacy (10 items), communicative literacy (6 items), critical literacy (11 items), and numeracy (8 items). Each dimension reflects essential aspects of medication literacy specific to this population, as identified through expert consensus.ConclusionThis study developed a preliminary, standardized tool for assessing medication literacy in patients with mental disorders during recovery, with the potential to identify individuals at risk of medication mismanagement and to enable targeted interventions and improved outcomes in China’s healthcare system. Although its psychometric properties have not yet been evaluated in this stage, future research will conduct empirical validation to establish its measurement reliability and validity.